2017
DOI: 10.3389/fimmu.2017.00898
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Mechanisms Underlying Chronic Pelvic Pain and Prostate Inflammation in Chronic Pelvic Pain Syndrome

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is the most common urologic morbidity in men younger than 50 years and is characterized by a diverse range of pain and inflammatory symptoms, both in type and severity, that involve the region of the pelvis, perineum, scrotum, rectum, testes, penis, and lower back. In most patients, pain is accompanied by inflammation in the absence of an invading infectious agent. Since CP/CPPS etiology is still not well established, available therapeutic options for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 136 publications
(191 reference statements)
3
77
0
3
Order By: Relevance
“…6 The etiology of CP/ CPPS is still unclear, and the possible mechanisms associated with CP/CPPS include defective urothelial integrity and function, pelvic floor muscle spasm or tenderness, peripheral and central sensitization and neuroplasticity, and autoimmune imbalance. [7][8][9][10] By amplifying inflammation, interleukin (IL)-17Aproducing T helper 17 (Th17) cells play a crucial role in the development and progression of several autoimmune diseases, such as multiple sclerosis (MS) 11 and systemic lupus erythematosus (SLE). 12 Some studies have reported controversial results regarding the role of Th17 cells in the development of CPPS.…”
Section: Introductionmentioning
confidence: 99%
“…6 The etiology of CP/ CPPS is still unclear, and the possible mechanisms associated with CP/CPPS include defective urothelial integrity and function, pelvic floor muscle spasm or tenderness, peripheral and central sensitization and neuroplasticity, and autoimmune imbalance. [7][8][9][10] By amplifying inflammation, interleukin (IL)-17Aproducing T helper 17 (Th17) cells play a crucial role in the development and progression of several autoimmune diseases, such as multiple sclerosis (MS) 11 and systemic lupus erythematosus (SLE). 12 Some studies have reported controversial results regarding the role of Th17 cells in the development of CPPS.…”
Section: Introductionmentioning
confidence: 99%
“…There are many types of experimental rodent prostatitis models including spontaneous prostatitis, miscellaneous prostatitis, hormone‐associated prostatitis and immune‐induced prostatitis (Vykhovanets, Resnick, Maclennan, & Gupta, ). EAP is the most commonly used model to mimic CP⁄CPPS since its typical characteristics are consistent with CP⁄CPPS (Breser et al, ). EAP is induced by multipoint subcutaneous injection of prostate antigen with an adjuvant, leading to T‐cell activation and inflammatory cell infiltration of the prostate gland (Kurita, Yamaguchi, Okamoto, Kotera, & Oka, ).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that TRPV1 plays a significant role in CP/CPPS‐induced pain. A rat model of experimental autoimmune prostatitis (EAP) has been used to study CP/CPPS for decades and has proven valid to mimic human CP⁄CPPS (Breser, Salazar, Rivero, & Motrich, ). We studied the expressions of TRPV1 in the prostate, bladder and dorsal root ganglion (DRG) of EAP rats to elucidate the pathogenesis of CP/CPPS.…”
Section: Introductionmentioning
confidence: 99%
“…Mentale Störungen gehen mit einer erhöhten Immunsystem(re)aktivität einher Viele, wenn nicht gar alle der stressassoziierten somatischen und psychiatrischen Erkrankungen [76][77][78][79][80][81][82] einschließlich PTBS, generalisierte Angststörung (GAS), Panikstörung, Phobien (Agoraphobie, Sozialphobie usw.) [83,84], Depression [85][86][87], Burnout [88,89], chronisches Erschöpfungssyndrom [90][91][92] und Schizophrenie [93], gehen mit einem über(re)aktiven Immunsystem und chronischen unterschwelligen Entzündungen einher.…”
Section: Stress Entzündung Und Psychische Gesundheitunclassified